EDITORIAL: Evil By Commission in International Relations - Junita Budi Rachman; Arry Bainus (Intermestic: Journal of International Studies, 2026)
The purpose of this essay is to explore the concept of evil in international relations, specifically focusing on evil by commission in various dimensions. In the field of international relations, the discussion of evil within the international political arena is often overlooked. In the study of International Relations, evil results from deliberate actions by agents such as states, corporations, or non-state actors, often obscured by complex bureaucracies. This framework aims to systematically analyze evil by distinguishing between material and non-material instruments and defining various impact locations. It seeks to frame evil as a subject for scientific inquiry, rather than a mere moral issue.